البعد المصلحي في نظم وآليات اختيار رئيس الدَّولة: دراسة تأصيلية تحليلية - حسن، بيدر محمد محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research aims to study the selection mechanism and the system of selecting the head of state based on the Maslaha theory. The selection process depends on humanitarian principles as a standard for the political process needed in selecting the head of state. Based on the analysis, the major factors for the success of the selection process are freedom, equality, Al-Shura and the social contract of the society. The researcher applied two analytical methods based on the Maslah theory; analytical methodology and theoretical methodology. The researcher used the Maslaha theory to evaluate the essential theories for selection of the head of state. Consequently, the development of the appropriate theory, which can balance between the system and the social contract, has been done through this research. The social contract plays a vital role in facilitating the process of reaching good governance. Therefore, a social environment that encompasses competition, Al-Shura selection, and the social contract between the government and its people, are vital. The integration of selection systems and mechanisms based on a framework of social and constitutional guarantees will allow for more appropriate selection of head of state. Also, the role of the supervisory and organizational institutions is vital, and it should be regulated based on integrity, responsibility and independence. The selection process for the head of the state in the time of the Four Righteous Caliphs is an application of a selection system within a social construct. This selection process allowed for the development of a selection mechanisms, which complies with social and constitutional guarantees, safeguarding the political process from deviation from constitutional principles. This study demonstrates that the successful application of constitutional and social guarantee would allow for a successful process of selection of the head of a state based on the Maslaha theory.